Current Studies on Pragmatics Competence in EFL Learning Context: A Review - Bayu Andika Prasatyo; Helena Verusha Ali; Dini Hidayati (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
Pragmatic competence has hitherto been one of the concerns that has received attention in the area as a vital element of linguistic competence. This conceptual study showcases a brief overview of pragmatics competence in EFL learning environment by highlighting what study designs have been utilized in contemporary research that focuses on pragmatic competence in the context of English as a Foreign Language (EFL) learning and what the implications of fostering pragmatic competence are elaborated in the English as a Foreign Language (EFL) classroom under the realm of pragmatics study. The design of the study utilizes library research method. The present study presents a collection of empirical research examining pragmatic competence within English as a Foreign Language (EFL) learning contexts. The research methodologies implemented in these studies mostly consist of descriptive qualitative techniques, mixed methods, with only a limited number of studies utilizing the quantitative approach. Furthermore, the impact of sociopragmatic competence is significant in enhancing the communication abilities of English as a Foreign Language (EFL) learners.